A Primer on Developing European Public Goods - Clemens Fuest; Jean Pisani-Ferry (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The EU has mostly been defined as a provider of economic integration amongst participating member states. Its cornerstones have been the removal of obstacles to cross-border flows of goods, services, labour and capital, and the development of common policies that ensure the smooth functioning of an integrated market, be it for trade, competition, infrastructures or consumer protection, to name the main ones only. Even the euro was initially conceived as a natural complement to the internal market and as a trigger for further integration. This policy report from Clemens Fuest (ifo Institute, LMU, EconPol) and Jean Pisani-Ferry (EUI, Bruegel) discusses the case for enhanced provision of European public goods and makes a number of proposals for concrete steps and initiatives.
Keywords: 330